Fluid mechanics - Douglas, J.F.; J. M. Gasiorek; J.A. Swaffield (London : Pitman Publishing Limited, 1979)
This is a textbook for all manner of engineers. Whether the reader is concerned with Civil, Mechanical, or chemical engineering, building services or environmental engineering, the principles of fluid mechanics remain the same.
Part I. Elements of fluid mechanics -- Part II. Behaviour of real fluids -- Part III. Steady flow in pipelines and open channels -- Part IV. Unsteady flow in bounded systems -- Part V. Fluid machinery -- Part VI. Dimensional analysis and similarity.
Includes index.
Keywords: ENGINEERING